The Performance and Efficiency of XYZ Bank Work Units - Riyanti, Evy; Hartoyo, Sri; Sasongko, Hendro (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Bank is an institution or business entity that has a big role in the financial system in the world, especially in Indonesia. The banking industry, which consists of government-owned banks and private banks with sharia and conventional systems, are mutually exclusive to survive the current tough competition. There have been various ways that have been done to attract attention to its customers. Bank XYZ realizes that the competition between companies is getting bigger, therefore the management of XYZ Bank issued a policy by building a new work unit. The operational sustainability of XYZ Bank in the Indonesian banking industry is closely related to the ability to maintain high competitiveness. Bank competitiveness can be reflected in the level of operational efficiency. This study uses secondary data from the XYZ Bank work unit and is analyzed by Data Envelopment Analysis. It is known that in the Bogor work unit, from the 17 times studied, 5 of them experienced inefficient conditions, while the Yogyakarta work unit was known to have 6 times that were inefficient. Keywords: data envelopment analysis, efficiency, work unit, banking industry, bank competitiveness